Conceptualizing caregiving activities for persons with dementia (PwD) through a patient work lens. (May 2020) - Ponnala, Siddarth; Block, Laura; Lingg, Aloysius J.; Kind, Amy J.; Werner, Nicole E.
Abstract: Informal caregivers are an integral part of care delivery for persons with dementia (PwD). Informal caregivers take part in a wide range of care activities both individually and collaboratively with other caregivers. Caregiving often involves high demands in the face of limited resources, which can lead to stress, burden, and burnout. To support caregivers, we need to conceptualize caregiving activities they perform, and the networks and roles through which they perform work. We performed a directed content analysis on interview data from twenty caregivers and applied a human factors approach to characterize informal caregiving work. Our results revealed 1) nuances in caregiving roles, 2) differences in caregiving networks, and 3) 13 categories of caregiving activities characterized by time commitments; physical, cognitive and socio-behavioral demands; and varying network dependencies. These findings can be applied in future studies to evaluate the needs of caregiving networks and how to better support them. Highlights: A patient-work approach conceptualizes the work and demands of caregiving. Findings suggest caregivers work in a network to perform patient work. There are many types of caregiving work with unique demands. Identifying caregiving demands can inform work-system design.